Electrochemical Membrane Technology for Carbon Dioxide Capture from Flue Gas. (March 2017) - Ghezel-Ayagh, Hossein; Jolly, Stephen; Patel, Dilip; Steen, William
Abstract: To address concerns about climate change resulting from emission of CO2 by fossil-fuel power plants, FuelCell Energy, Inc. (FCE) has developed Combined Electric Power and Carbon-dioxide Separation (CEPACS) system concept. The CEPACS system utilizes Electrochemical Membrane (ECM) technology derived from the Company's Direct FuelCell ® products. The system separates the CO2 from the flue gas of other plants and produces electric power using a supplementary fuel. FCE is currently evaluating the use of ECM to cost effectively separate CO2 from the flue gas of Pulverized Coal (PC) power plants under a U.S. Department of Energy contract. The overarching objective of the project is to verify that the ECM can achieve at least 90% CO2 capture from the flue gas with no more than 35% increase in the cost of electricity. The project activities have included: 1) techno-economic analysis for an ECM-based CO2 capture system applied to a 550 MW existing PC plant, 2) laboratory scale operational and performance tests of a membrane assembly, 3) performance tests of the membrane to evaluate the effects of impurities present in the coal plant flue gas, and 4) bench scale testing of an ECM-based CO2 separation and purification system.